Komparasi Penyelenggaraan Pembelajaran Sekolah Luar Biasa di (SLB-B) Budi Nurani Dan Pendidikan Inklusif di SMP Negeri 3 Pabuaran dalam Meningkatkan Mutu Pembelajaran Disabilitas - Eti Robiatul Adawiah; Siti Qomariyah; Tintin Handiyati; Siti Nuraeni Mitra; Eneng Sumarni (Journal on Education, 2023)
Special schools (SLB) are only located in the city center, so that those with special needs in remote areas cannot reach their location. This is the reason why inclusive education is held. (Mohammad Divine Destiny, 2013). This study aims to find out the comparison of the implementation of special school learning at (SLB-B) Budi Nurani and inclusive education at SMP Negeri 3 Pabuaran in improving the quality of learning with disabilities. This study used a descriptive qualitative analysis approach with inductive data collection. The results of this study are that the Budi Nurani SLB-B School organizes special education for the blind with complete infrastructure, but not solid enough. Meanwhile, inclusive education at SMPN 3 Pabuaran provides education for the disabled and learning difficulties. SMPN 3 Inclusive Education has limitations: infrastructure and funds. The two schools optimize the learning process. so as to give birth to students who are able to live independently and compete in society. Both use the National Education Curriculum. The learning process for SLB students with a specialization in the deaf, how to communicate using sign language while reading the lips of the interlocutor. Meanwhile, students with special needs who carry out the learning process in Inclusive Education schools carry out the learning process without having to be specific in their class. Students at both the Budi Nurani SLB-B School and inclusive education at SMPN 3 Pabuaran are diligent in worship and can accept God's decrees/qadla